An Estimating the Volume of Water Torrents in the Rizan River Basin and its Environmental Risks - Halaw Hussain Karem; Nzar Yasin Muhammad (Zanco Journal of Humanity Sciences)
This study aims to determine the basic hydrological characteristics in the Rezan River Basin and their role in the occurrence of torrential and flood risks and to determine the most important effects that torrents and floods leave on the nature of the region and human activities in it. The inductive approach and statistical method were used to trace the precise parts of the topic to reach general conclusions. The US Soil Service model (SCS-CN) method was adopted to estimate the volume of surface runoff using a program (WMS). The model (SCS-CN) was applied ten times using rain showers ranging from (20-200 mm), with a difference of (20 mm), in addition to a real rain peak.